A novel way to present flood hazards using 3D-printing with transparent layers of return period isolines - Burian, Tomas; Gorin, Svemir; Radevski, Ivan; Vozenilek, Vit (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
This paper examines the 3D printed results of a floodplain analysis usually used for hydrological studies to calculate the probabilities in high water stage features. The analysis was performed using probability distributions, including Pearson type III distribution, Log-Pearson type III distribution, Gaussian (normal) distribution, Gumbel distribution, and Log-normal distribution. The maximum theoretical stages of best fitting distribution for different return periods were mapped to the Vardar and Boshava rivers in the Tikvesh Valley. Data to create the model were extracted from digital elevation models of the Vardar river target area. The extracted 3D surface model was covered with a map showing all the flooded areas in the relevant territory for different return periods as transparent layers. The data were converted into a physical model (relief map) using 3D printing methods for visualisation.